Efficiency progress of inverted perovskite solar cells. Issue 11 (6th October 2020) - Lin, Xuesong; Cui, Danyu; Luo, Xinhui; Zhang, Caiyi; Han, Qifeng; Wang, Yanbo; Han, Liyuan
Abstract : A comprehensive review on the efficiency progress of inverted perovskite solar cells towards future development and commercialization. Abstract : Inverted perovskite solar cells (IPSCs) have attracted great attention in recent years due to their reliable operational stability, negligible hysteresis and low-temperature fabrication process. To accelerate their commercialization, the focus of research on IPSCs has been to enhance the power conversion efficiency over the past few years. Herein, an overview of efficiency progress in IPSCs is given including the structure design, the fabrication of perovskite films and the modification of charge transport materials. Specifically, the effects of interface passivation on the performance of those devices have been emphasized. Finally, perspectives on the further development and commercialization of IPSCs are proposed, such as developing new electron transport materials and rear electrode materials, and employing field effect passivation materials and inorganic hole transport materials.